The use of feed and water additives for live fish transport - Myriam Vanderzwalmen; Lewis Eaton; Carrie Mullen; Fiona Henriquez; Peter Carey; Donna Snellgrove; Katherine A. Sloman (Reviews in Aquaculture, 2019)
The transport of live fish for aquaculture, either for food or as companion animals, presents a major issue for animal welfare. The stressors associated with live transportation are well documented with a focus on maintaining water quality during transport to reduce stress. Far less considered is our ability to enhance health and welfare during transport through the use of dietary and water additives prior to and during transport. With increasing interest in the use of plant essential oils as feed additives in food fish aquaculture and the increased availability of products claiming to alleviate stress in ornamental species, there is a need for scientific investigation into these potential welfare‐promoting methods. Here, we summarise current knowledge on the use of food additives, water conditioners, antibiotics, antimicrobials and probiotics to promote fish health during transport. This review aims to highlight the gaps in our knowledge surrounding promising ways of promoting fish health during transport and to stimulate new research in this area.